2021
DOI: 10.3390/microorganisms9030592
|View full text |Cite
|
Sign up to set email alerts
|

Effective Small Molecule Antibacterials from a Novel Anti-Protein Secretion Screen

Abstract: The increasing problem of bacterial resistance to antibiotics underscores the urgent need for new antibacterials. Protein export pathways are attractive potential targets. The Sec pathway is essential for bacterial viability and includes components that are absent from eukaryotes. Here, we used a new high-throughput in vivo screen based on the secretion and activity of alkaline phosphatase (PhoA), a Sec-dependent secreted enzyme that becomes active in the periplasm. The assay was optimized for a luminescence-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The UV/Vis absorption spectra of AgNPs are shown in Figure S5a-c. The maximum absorption results of the studied nanocomposites were found at 473 nm, 442 nm, and 414 nm for citrate-capped AgNPs, PVP-capped AgNPs in water, and PVP-capped AgNPs in EG, respectively [55,66]. It has been reported that the absorption spectrum of spherical silver nanoparticles showed a maximum between 400 nm and 500 nm with a blue or red shift when the particle size diminished or increased, respectively [67,68].…”
Section: Secm Investigation Of Biofilm Degradation By Silver Nanopart...mentioning
confidence: 85%
See 3 more Smart Citations
“…The UV/Vis absorption spectra of AgNPs are shown in Figure S5a-c. The maximum absorption results of the studied nanocomposites were found at 473 nm, 442 nm, and 414 nm for citrate-capped AgNPs, PVP-capped AgNPs in water, and PVP-capped AgNPs in EG, respectively [55,66]. It has been reported that the absorption spectrum of spherical silver nanoparticles showed a maximum between 400 nm and 500 nm with a blue or red shift when the particle size diminished or increased, respectively [67,68].…”
Section: Secm Investigation Of Biofilm Degradation By Silver Nanopart...mentioning
confidence: 85%
“…Under aerobic conditions, oxygen is the final electron acceptor. This results in the transport of up to eight protons [55]. The ETC comprises membrane-bound cytochromes (a-, b-, d-, o-type), dehydrogenases, quinones, and flavins.…”
Section: Secm Investigation Of Biofilm Degradation Induced With Azidementioning
confidence: 99%
See 2 more Smart Citations
“…Biofilms on a coverslip were incubated in a solution with 4 mM sodium azide, a potent inhibitor of bacterial growth [49]. Sodium azide inhibits bacterial growth by inhibiting the activity of SecA, an…”
Section: Secm Investigation Of Biofilm Degradation Induced With Azidementioning
confidence: 99%